Suscetibilidade de larvas de Simuliidae (Diptera) a um novo formulado a base de Bacillus thuringiensis subesp. israelensis, e aspectos bioecológico de criadouros em riachos de Cascavel, PR - Lis, Paula Costa (2023)
The hematophagous species of Simuliidae, when abundant, are responsible for economic, public and veterinary health losses. They perform important ecological functions, but in many places, impacted by anthropic actions, which favor generalist species, the monitoring and control of these populations is necessary. Currently, the products recommended for control are bioinsecticides based on Bacillus thuringiensis subsp. israelensis (Bti), used for the larval stage of the insect, and for Brazil there are two imported products available. Bacillus thuringiensis israelensis is a gram-positive soil bacterium that forms specific entomopathogenic spores. This project aimed to evaluate the susceptibility of Simuliidae larvae (Diptera) to a new formulation based on Bti in laboratory conditions and address bioecological aspects of simulid breeding sites in streams of Cascavel – PR. The fermented Bti was produced in the Laboratory of Genetics and Taxonomy of Bacteria at the State University of Londrina – UEL and its toxicity was verified in the Medical Entomology laboratory at 2,700 International Toxic Units/mg. The product was processed by the Laboratory of Chemical Ecology and Synthesis of Natural Products at the Federal University of Paraná (UFPR), in Curitiba – PR, where two types of formulations were prepared: liquid and solid. To carry out the bioassays were used plastic cups and aerators, the source of larvae and water was from the stream itself, (24°49'15.9"S and 53°37'51.2"W). In liquid suspensions, mortality observed did not exceed 20%, not differing significantly from the witness. Among the solid formulates, the observed mortality did not exceeded 19.6% for a concentration of 30 mg/L, not differing significantly from the witness. For a concentration of 40 mg/L, it was observed mean mortality of 34.3%. For concentrations of 50 and 60 mg/L to mean mortality was 50.6% and 64.2%, respectively, and both did not significantly differed from the commercial standard formulation Vectobac® 12 AS (Lot 301-886-N930), in the exposure time of 1 minute and after the period of 18 hour evaluation. On the other hand, concentrations of 70 and 80 mg/L presented results comparable to those of the control group, with 35.7 and 31.7% of mortality respectively. Absence of larvicidal activity it was probably due to the unavailability of Bti for ingestion by the larvae due to excessive particle size. The stream sampled, for evaluation of quality parameters, showed external fecal contamination during the eight weeks of monitoring and parameters that could interfere with the efficiency of control with Bti in place. Were identified six species, among them Simulium pertinax, Simulium subpallidum; Simulium nigrimanum; Simulium rubritorax; Simulium perflavum; and Simulium inaequale, being the first identification of species of the family Simuliidae, for the municipality of Cascavel - PR. The data obtained in the work indicated the potential of the effervescent formulation under laboratory conditions, requiring enhancement. Bioecological estimates tolerate the diagnosis and environmental monitoring in the optimization of control protocols from Simulium sp.